ChemInform Abstract: Diastereo‐ and Enantioselective Construction of an Indole‐Based 2, 3‐Dihydrobenzofuran Scaffold via Catalytic Asymmetric [3 + 2] Cyclizations of Quinone Monoimides with 3‐Vinylindoles. Issue 25 (June 2016) - Sun, Xiao‐Xue; Zhang, Hong‐Hao; Li, Guo‐Hao; Meng, Li; Shi, Feng
Abstract: The title reaction proceeds well with various vinylindoles using spiro‐chiral phosphoric acid as a powerful chiral catalyst.